Aplikasi Wireless Media Storage Menggunakan Smartphone Android - Wibowo, Cahyanto Adi, Dian Purworini, S. Sos. MM (2017)
The current state of this fast-paced and the file size is very large, sometimes requiring an additional storage devices for mobile handsets us, call it Smartphone, Tablet, Ultrabook, or even a computer device such as a PC or Laptop to store various types of files either, documents work, text files, spreadsheets, presentations, images or photographs, videos, music or even audio. And external storage devices like portable external hard drive also known as portable hard drive is known as a portable storage device that can store files with a capacity that is comfortable and large, but the drawback. This storage can only be connected with the computer such as a PC, laptop or with OTG-enabled smartphone devices that support NTFS format. The main Objective of this study is to create an android application system, which is useful for sharing files folder. Users can freely freely upload and download files to the storage media. The results of this study are Android-based X-plore File Manager which can be used for sharing folders wirelessly.